2011
DOI: 10.1590/s1517-86922011000400015
|View full text |Cite
|
Sign up to set email alerts
|

Parâmetros, considerações e modulação de programas de exercício físico para pacientes oncológicos: uma revisão sistemática

Abstract: Introduction: This investigation searched for data that would describe the use of physical exercise, not as preventive method, but as a supporting therapeutic modality in the coping of the cancer (CA) and its treatment from diagnosis to recovery, since there is massive harm and side effects experienced by the patients that can be modified through the practice of physical exercises. Objective: To identify and select references which demonstrate necessary parameters for prescription of physical exercise programs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 22 publications
(79 reference statements)
0
7
0
4
Order By: Relevance
“…Breast cancer is currently treated as a systemic disease and surgical treatment is therefore followed by an adjuvant therapy such as chemotherapy, radiotherapy or hormone therapy 3 . Facing breast cancer can cause changes in body image, functional loss, and psychological trauma in the woman 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is currently treated as a systemic disease and surgical treatment is therefore followed by an adjuvant therapy such as chemotherapy, radiotherapy or hormone therapy 3 . Facing breast cancer can cause changes in body image, functional loss, and psychological trauma in the woman 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…The use of physical exercise appears as a therapeutic modality in improving the physical and emotional capabilities to assist in coping with diagnosis and recovery of cancer patients. 16 As a result, a study in Brazil sought to identify the QOL of patients with cancer. It showed physiotherapy and physical activity as a strategy for improving QOL and reducing the impact of the disease on the lives of these patients.…”
Section: Physical Activity As Improving Quality Of Life Of Men With Mmentioning
confidence: 99%
“…Conclui-se que as mulheres com câncer de mama eram insuficientemente ativas e apresentavam bons escores de qualidade de vida geral, sendo que as ativas apresentaram melhor função física, desempenho de papéis e menor presença de sintomas, perda de apetite e dor. the disposition to face these changes 7 . In this respect, investigations in Brazil on improving physical capacities, essential to cope with cancer from diagnosis to recovery 7 , suggested that following a healthy lifestyle is a protective factor against new cancer cases in the country 8 .…”
Section: Introductionmentioning
confidence: 99%
“…the disposition to face these changes 7 . In this respect, investigations in Brazil on improving physical capacities, essential to cope with cancer from diagnosis to recovery 7 , suggested that following a healthy lifestyle is a protective factor against new cancer cases in the country 8 . In addition to being a protective factor, physical activity (PA) may be related to increased life expectancy after BC diagnosis 9 .…”
Section: Introductionmentioning
confidence: 99%